Middle Ear Effusion in Children With Congenital Cytomegalovirus Infection. Issue 4 (April 2020) - Chung, Winnie; Leung, Jessica; Lanzieri, Tatiana M.; Blum, Peggy; Demmler-Harrison, Gail; Ahmed, Shahzad; Baer, Hanna; Bhatt, Amit R.; Brown, Frank; Catlin, Francis; Caviness, Alison C.; Coats, David K.; et al.
Abstract : Background: Sensorineural hearing loss (SNHL) is well described in children with congenital cytomegalovirus (CMV) infection, but limited data are available on middle ear effusion (MEE) occurrence in this population. We assessed the prevalence of MEE and the degree of transient hearing change associated with MEE among children with congenital CMV infection. Methods: Children with congenital CMV infection enrolled in a longitudinal study received hearing and tympanometric testing during scheduled follow-up visits annually up to 6 years of age. We used a generalized linear mixed-effect logistic regression model to compare the odds of MEE, defined as type B tympanogram (normal ear canal volume with little tympanic membrane movement) among patients categorized as symptomatic or asymptomatic based on the presence of congenital CMV-associated signs in the newborn period. Results: Forty-four (61%) of 72 symptomatic and 24 (28%) of 87 asymptomatic patients had ≥1 visit with MEE. After controlling for the number of visits, symptomatic patients had significantly higher odds of MEE (odds ratio: 2.09; 95% confidence interval: 1.39–3.14) than asymptomatic patients. Transient hearing decrease associated with a type B tympanogram ranged from 10 to 40 dB, as measured by audiometric air-bone gap in 11 patients. Conclusions: Among children with congenital CMV, MEE can result in transient hearing decrease, which can reduce the efficacy of a hearing aid in those with SNHL. It is warranted that children with congenital CMV infection and SNHL receive routine audiologic and tympanometric testing to better manage hearing aid amplification levels.